The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2014 Conference on Interaction Design and Children 2014
DOI: 10.1145/2593968.2593983
|View full text |Cite
|
Sign up to set email alerts
|

Search result visualization with characters for children

Abstract: In this paper, we explore alternative ways to visualize search results for children. We propose a novel search result visualization using characters. The main idea is to represent each web document as a character where a character visually provides clues about the webpage's content. We focused on children between six and twelve as a target user group. Following the user-centered development approach, we conducted a preliminary user study to determine how children would represent a webpage as a sketch based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Our study complements previous investigations showing that interface personification preference may be more related to individual differences than age [56]. We did not see specific age effects found in other previous work (e.g., older children considering personification to be too childish) [20]. There was a substantial split regarding personalization and there were also a fair number of participants who preferred the non-personified condition (i.e., a family of four is not unlikely to have one person in this category).…”
Section: Building For the Whole Familysupporting
confidence: 89%
See 1 more Smart Citation
“…Our study complements previous investigations showing that interface personification preference may be more related to individual differences than age [56]. We did not see specific age effects found in other previous work (e.g., older children considering personification to be too childish) [20]. There was a substantial split regarding personalization and there were also a fair number of participants who preferred the non-personified condition (i.e., a family of four is not unlikely to have one person in this category).…”
Section: Building For the Whole Familysupporting
confidence: 89%
“…Older participants are more likely than younger children to have a negative affective response to speech interfaces that violate privacy expectations (e.g., know information that the child didn't explicitly tell them) [34]. Outside of speech interfaces, at least a few investigations have suggested that personified search agents may help children interpret query results and found that this approach worked best with 8-and 9-year-olds (older children found it to be too "childish") [20]. Systems can be fairly accurate at distinguishing between adult and children's speech [43], however little is known about how a system could then adjust its personification and personalization in the most appropriate way to ages or preferences of users.…”
Section: Personification and Personalization In Speech Interfacesmentioning
confidence: 99%